Preparation and Characterization of Nanocrystalline Cellulose from Cassava Stem Wastes by Electromagnetic Induction - Lismeri, Lia; Rahmi, Hertantri Yulia; Gomiyati, Nada Afifah; Darni, Yuli; Febriningrum, Panca Nugrahini; Azhar, Azhar (Jurnal Rekayasa Kimia & Lingkungan, 2021)
Cassava stems were one of the largest agricultural by products in Indonesia, especially in Lampung Province. It is known that cassava stems have a fairly high lignocellulose content, especially cellulose which reaches 39.29%. The high cellulose content in cassava stems has great potential to be used as raw material for Nanocrystalline Cellulose (NCC). The preparation of nanocrystalline cellulose consists of four main stages, namely: pre-hydrolysis, delignification, bleaching, and acid hydrolysis. The pre-hydrolysis stage was carried out by boiling a solution of CH3COOH and cassava stem powder for 60 minutes at a temperature of 105oC. Cassava stem powder was then delignified using a 25% NaOH solution heated to a temperature of 105oC for 1 hour. The bleaching stage used a 3.5% NaOCl solution at a temperature of 50oC for 60 minutes and was carried out twice. The last step is acid hydrolysis using 2.5N HCl solution for 15 minutes at a temperature of 105oC, then the electromagnetic induction treatment is varied with temperature variations of 30oC, 50oC, and 70oC for 60 minutes. The prepared nanocrystalline cellulose were tested for lignocellulose, XRD and PSA. From the test results, the best variation of nanocrystal cellulose preparation was acid hydrolysis treatment with 70oC electromagnetic induction for 60 minutes, namely an increase in the percentage of cellulose 62.93%, crystallinity 90.68%, and an average particle size of 18.04m with some particles measuring nanometers. From the results of the research, it was concluded that electromagnetic induction increased crystallinity and decreased the size of nanocrystalline cellulose.